Preparation method of infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction

By designing surface ligand-controlled quantum doping structure and bias voltage regulation technology, the problems of bulkiness and low measurement sensitivity of traditional spectrometers are solved, and miniaturized and efficient infrared spectral resolution are achieved.

CN118486760BActive Publication Date: 2025-02-14WESTLAKE INSTITUTE FOR OPTOELECTRONICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410655372.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-02-14
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

Traditional spectrometers require mechanically movable components, which makes them bulky and difficult to miniaturize, and require splitting of the light path for each detector, reducing the intensity of light signals and measurement sensitivity.

Method used

The doping concentration and type of quantum dot film is regulated by surface ligand, and the detector structure of "strong P-type-substrength P-type-weak P-type-eigen-N-type layer" is designed, and the quantum is realized by bias regulation is used to achieve the The infrared spectral device with a bandgap doped double gradient PN junction is prepared by the response of the point gradient doped PN junction to different spectra.

Benefits of technology

The infrared detector response to different band spectra is realized, without the need for complex spectroscopy paths or filters, and the spectrum can be distinguished by only adjusting the bias voltage, achieving the effect of miniaturization and high photon utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118486760B_ABST
    Figure CN118486760B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction, comprising: using surface ligands to control the doping concentration and type of quantum dot film, designing and obtaining a detector structure of "strong P-type-sub-strong P-type-weak P-type-intrinsic-N-type layer" and "large bandgap-medium-large bandgap-medium bandgap-medium-small bandgap-small bandgap"; using bias control to achieve different responses of quantum dot gradient-doped PN junction infrared detector to different spectra, and preparing an infrared spectroscopy device with bandgap-doped double-gradient PN junction. The spectroscopy device prepared by the present invention does not require a complex spectroscopic optical path or microstructures such as filters designed for specific spectral bands. It only needs to regulate the bias voltage of the detector to distinguish the spectrum, while achieving miniaturization and high photon utilization efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of infrared spectroscopy devices, and in particular relates to a method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction. Background Art

[0002] Spectrometers are widely used in scientific and industrial applications, such as spectral detection, chemical sensing, and hyperspectral imaging. Traditional spectral analysis solutions generally require the use of mechanically movable parts, such as optical gratings or Michelson interferometers. This solution often makes the spectrometer too bulky. Miniaturization is an important direction for spectrometers. For example, using photodetector arrays, through dispersive optics, narrow-band filters, etc., each individual detector is equipped with tailored optical elements to reconstruct spectral information for the entire array. However, for each detector, to detect different spectra, the light must be split into multiple paths, which reduces the intensity of the light signal and thus reduces the measurement sensitivity. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction, comprising:

[0004] By using surface ligands to regulate the doping concentration and type of quantum dot films, the detector structures of "strong P-type-sub-strong P-type-weak P-type-intrinsic type-N-type layer" and "large band gap-medium-large band gap-medium band gap-medium-small band gap-small band gap" were designed;

[0005] By using bias voltage regulation, different responses of quantum dot gradient-doped PN junction infrared detectors to different spectra are achieved, and an infrared spectroscopy device with a bandgap-doped double-gradient PN junction is prepared.

[0006] Preferably, the method further includes preparing materials before using surface ligands to regulate the doping concentration and type of the quantum dot film;

[0007] The material preparation includes preparing 90% tri-n-octyl phosphide (TOP) with a technical grade of 90%, 99.999% granular tellurium (Te), ACS reagent grade>=99.5% mercuric chloride (HgCl2), 70% oleylamine (OAM), 98% dodecanedetate (DDT), HPLC99.9% tetrachloroethylene (TCE), and preparing TOPTe solution.

[0008] Preferably, the preparation process of the TOPTe solution includes: stirring tellurium (Te) particles and tri-n-octylphosphine (TOP) in a nitrogen glove box at room temperature to prepare a Te solution dissolved in tri-n-octylphosphine (TOP) to form a bright yellow solution with a concentration of 1 M, which is the TOPTe solution.

[0009] Preferably, the synthesis process of the quantum dots comprises:

[0010] In a glove box under a nitrogen environment, 27 mg and 0.1 mmol of mercuric chloride (HgCl2) were taken, and 4 ml of oleylamine (OAM) was added to obtain a mixture; the mixture was placed on a hot plate, stirred with a magnetic stirrer, and the temperature of the hot plate was adjusted to 105° C., and heated at 105° C. for 1 h until a transparent light yellow solution was formed;

[0011] Take 500 μL TOP, 500 μL DDT, and 4 mL TCE and put them into a glass bottle and store them in a refrigerator to prepare a quenching solution;

[0012] After the transparent light yellow solution becomes clear by the hot injection method, the reaction temperature is lowered as needed, and the thermal equilibrium is carried out for half an hour. After the thermal equilibrium is completed, 100 μL of TOPTe solution is injected, and the reaction is continued for the preset reaction time according to the needs. After the reaction is completed, the quenching solution is added to cool the reaction, and the solution is taken out from the glove box and cooled in a water bath to obtain short-wave quantum dots.

[0013] Preferably, the synthesis of the quantum dots comprises:

[0014] Synthesis of 1.5μm short-wave quantum dots, synthesis of 1.7μm short-wave quantum dots, synthesis of 2.0μm short-wave quantum dots, synthesis of 2.3μm short-wave quantum dots, and synthesis of 2.5μm short-wave quantum dots;

[0015] The reaction temperature for synthesizing the 1.5 μm short-wavelength quantum dots was 55° C. and the reaction time was 4 min.

[0016] The reaction temperature for synthesizing the 1.7 μm short-wavelength quantum dots is 60° C. and the reaction time is 4 min.

[0017] The reaction temperature for synthesizing the 2.0 μm short-wavelength quantum dots is 65° C. and the reaction time is 5 min.

[0018] The reaction temperature for synthesizing the 2.3 μm short-wavelength quantum dots was 75° C. and the reaction time was 4 min.

[0019] The reaction temperature for synthesizing the 2.5 μm short-wavelength quantum dots is 80° C. and the reaction time is 4 min.

[0020] Preferably, the preparation process of the “strong P type-secondary strong P type-weak P type-intrinsic type-N type layer” includes:

[0021] Prepare a PVP layer, and based on the PVP layer, prepare “strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers” respectively through “1.5 μm, 1.7 μm, 2.0 μm, 2.3 μm, and 2.5 μm” quantum dot films;

[0022] The process of preparing "strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers" respectively through "1.5μm, 1.7μm, 2.0μm, 2.3μm, and 2.5μm" quantum dot films includes:

[0023] Preparation of 1.5μm strong P-type film, preparation of 1.7μm secondary P-type film, preparation of 2.0μm weak P-type film, preparation of 2.3μm intrinsic type film, and preparation of 2.5μm N-type film.

[0024] Preferably, the process of preparing the PVP layer comprises:

[0025] Polyvinyl pyrrolidone polymer was dissolved in ethanol with a concentration of 0.1 M and spin-coated on a sapphire Al2O3 substrate at 3000 r / min;

[0026] After curing on a hot plate at 50°C for 5 min, the entire sheet was peeled off from the sapphire substrate to obtain the target polymer;

[0027] The quantum dot film is coated on the surface of the target polymer to assemble the quantum dot film.

[0028] Preferably, the preparation process of the 1.5 μm strong P-type thin film includes:

[0029] On a sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100nm thick, 1.5μm quantum dot film was spin coated on the target polymer surface at a speed of 2000r / min, and then the whole was placed in a ventilation device and treated with a 15% AsH3 / N2 mixed gas for 2min to obtain a strong P-type doped film;

[0030] The preparation process of the 1.7 μm P-type thin film includes:

[0031] On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100 nm thick, 1.7 μm quantum dot film was spin coated on the target polymer surface at a speed of 2000 r / min. The whole was then placed in a ventilation device and treated with a 10% AsH3 / N2 mixed gas for 2 minutes to obtain a sub-P type doped film.

[0032] The preparation process of the 2.0 μm weak P-type thin film includes:

[0033] On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100 nm thick, 2.0 μm quantum dot film was spin coated on the target polymer surface at a speed of 2000 r / min. The whole was then placed in a ventilation device and treated with a 2% AsH3 / N2 mixed gas for 2 minutes to obtain a weak P-type doped film.

[0034] The preparation process of the 2.3 μm intrinsic film includes:

[0035] On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 200 nm thick, 2.3 μm quantum dot film was spin coated on the target polymer surface at a speed of 1000 r / min, and then the whole was placed in a ventilation device and treated with a 1% Cl2 / N2 mixed gas for 2 minutes to obtain an intrinsic type doped film;

[0036] The preparation process of the 2.5 μm N-type thin film includes:

[0037] 50nm of indium tin oxide (ITO) was magnetron sputtered on a sapphire Al2O3 substrate as the substrate of the PV device, and a 100nm thick, 2.5μm quantum dot film was directly spin-coated on the substrate at a speed of 2000r / min. Then the whole was placed in a ventilation device and treated with a 2% Cl2 / N2 mixed gas for 2 minutes to obtain an N-type doped film.

[0038] Preferably, the process of preparing an infrared spectroscopy device having a bandgap doped double gradient PN junction comprises:

[0039] Based on the N-type layer, a 2.3 μm intrinsic layer film was peeled off from the sapphire substrate, and the N-type layer and the intrinsic layer were treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds respectively to remove excess surface ligands and stable Fermi levels; without blowing the film dry, the intrinsic layer film surface with the PVP polymer was placed close to the N-type film surface to obtain a first assembly; the surface of the first assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a superposition of two layers of films with different doping states;

[0040] Based on the superposition of two layers of thin films with different doping states, a 2.0 μm weak P-type thin film was peeled off from the sapphire substrate, and the 2.0 μm weak P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the weak P-type film surface with PVP polymer was closely attached to the 2.3 μm intrinsic layer film on the upper surface of the first assembly to obtain a second assembly; the surface of the second assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a superposition of three layers of thin films with different doping states;

[0041] Based on the stacking of three layers of thin films with different doping states, a 1.7 μm sub-P-type thin film was peeled off from a sapphire substrate, and the sub-P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the sub-P-type thin film surface with PVP polymer was closely attached to the 2.0 μm weak P-type thin film on the upper surface of the second assembly to obtain a third assembly; the surface of the third assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a stacking of four layers of thin films with different doping states;

[0042] Based on the stacking of four layers of thin films with different doping states, a 1.5 μm strong P-type thin film was peeled off from the sapphire substrate, and the strong P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the surface of the sub-P-type thin film with PVP polymer was closely attached to the 1.7 μm sub-P-type thin film on the upper surface of the third assembly to obtain a fourth assembly; the surface of the fourth assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a stacking of five layers of thin films with different doping states;

[0043] Then, 50 nm of gold (Au) was evaporated on the top as a contact point to prepare an infrared spectroscopy device with a bandgap doped double-gradient PN junction.

[0044] Compared with the prior art, the present invention has the following advantages and technical effects:

[0045] The present invention uses atmosphere treatment to achieve different doping concentrations and types of quantum dot films, and designs a detector structure of "strong P-type-sub-strong P-type-weak P-type-intrinsic type-N-type layer". The gradient doped PN junction detector is biased and regulated. As the bias increases, the band gap increases from a large band gap to a small band gap. Different band gaps correspond to different wavelengths, forming a doping band gap dual gradient regulation, and realizing the response of the infrared detector to spectra of different bands.

[0046] The present invention does not require complicated spectroscopic optical paths or microstructures such as filters designed for specific spectral bands. The spectrum can be resolved by simply adjusting the bias voltage of the detector, while achieving miniaturization and high photon utilization efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0048] Figure 1 A schematic diagram of the structure of preparing thin films of different doping types according to an embodiment of the present invention;

[0049] Figure 2 is a graph of thin film FETs of different doping types according to an embodiment of the present invention;

[0050] Figure 3 A schematic diagram of a film assembly according to an embodiment of the present invention;

[0051] Figure 4 A schematic diagram of the device structure and a working principle diagram of an embodiment of the present invention;

[0052] Figure 5 is an IV curve diagram of an embodiment of the present invention;

[0053] Figure 6 Graphs showing different response spectra under different bias voltages according to an embodiment of the present invention. DETAILED DESCRIPTION

[0054] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0055] It should be noted that the steps shown in the flowcharts of the accompanying drawings can be executed in a computer system such as a set of computer executable instructions, and that, although a logical order is shown in the flowcharts, in some cases, the steps shown or described can be executed in an order different from that shown here.

[0056] Embodiment 1

[0057] like Figure 1-6 As shown, this embodiment provides a method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction, comprising:

[0058] By using surface ligands to regulate the doping concentration and type of quantum dot films, the detector structures of "strong P-type-sub-strong P-type-weak P-type-intrinsic type-N-type layer" and "large band gap-medium-large band gap-medium band gap-medium-small band gap-small band gap" were designed;

[0059] By using bias voltage regulation, different responses of quantum dot gradient-doped PN junction infrared detectors to different spectra are achieved, and an infrared spectroscopy device with a bandgap-doped double-gradient PN junction is prepared.

[0060] Furthermore, the method of using surface ligands to control the doping concentration and type of the quantum dot film also includes material preparation;

[0061] Material preparation includes preparing 90% technical grade tri-n-octyl phosphide (TOP), 99.999% particulate tellurium (Te), ACS reagent grade >= 99.5% mercuric chloride (HgCl2), 70% oleylamine (OAM), 98% dodecanedetate (DDT), HPLC 99.9% tetrachloroethylene (TCE), and preparing TOPTe solution.

[0062] Furthermore, the preparation process of TOPTe solution includes: stirring tellurium (Te) particles and tri-n-octylphosphine (TOP) in a nitrogen glove box at room temperature to prepare a Te solution dissolved in tri-n-octylphosphine (TOP) to form a bright yellow solution with a concentration of 1 M, which is the TOPTe solution.

[0063] Furthermore, the synthesis process of quantum dots includes:

[0064] In a glove box under a nitrogen environment, take 27 mg and 0.1 mmol of mercuric chloride (HgCl2) and add 4 ml of oleylamine (OAM) to obtain a mixture; put the mixture on a hot plate, add a magnetic stirrer and adjust the temperature of the hot plate to 105°C, and heat at 105°C for 1 h until a transparent light yellow solution is formed;

[0065] Take 500 μL TOP, 500 μL DDT, and 4 mL TCE and put them into a glass bottle and store them in a refrigerator to prepare a quenching solution;

[0066] After the transparent light yellow solution becomes clear, the reaction temperature is lowered as required by the hot injection method, and the thermal equilibrium is maintained for half an hour. After the thermal equilibrium is completed, 100 μL of TOPTe solution is injected, and the reaction is continued for the preset reaction time according to the requirements. After the reaction is completed, a quenching solution is added to cool the reaction, and the solution is taken out of the glove box and cooled in a water bath to obtain short-wave quantum dots. The size of the HgTe colloidal quantum dots can be controlled by controlling the synthesis temperature and reaction time.

[0067] Further, the synthesis of quantum dots includes:

[0068] Synthesis of 1.5μm short-wave quantum dots, synthesis of 1.7μm short-wave quantum dots, synthesis of 2.0μm short-wave quantum dots, synthesis of 2.3μm short-wave quantum dots, and synthesis of 2.5μm short-wave quantum dots;

[0069] Among them, the reaction temperature for synthesizing 1.5μm short-wavelength quantum dots was 55°C and the reaction time was 4min;

[0070] The reaction temperature for synthesizing 1.7 μm short-wavelength quantum dots was 60°C and the reaction time was 4 min;

[0071] The reaction temperature for synthesizing 2.0 μm short-wavelength quantum dots was 65 °C and the reaction time was 5 min;

[0072] The reaction temperature for synthesizing 2.3 μm short-wavelength quantum dots was 75 °C and the reaction time was 4 min;

[0073] The reaction temperature for synthesizing 2.5 μm short-wavelength quantum dots was 80°C and the reaction time was 4 min.

[0074] Quantum dots are based on the quantum confinement effect. The size of quantum dots adjusts the band gap. The larger the size, the smaller the band gap. Vertical stacking can achieve band gap regulation. The next step is to regulate the doping of quantum dot films.

[0075] Furthermore, the preparation process of “strong P type-secondary strong P type-weak P type-intrinsic type-N type layer” includes:

[0076] Prepare the PVP layer, and based on the PVP layer, prepare the "strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers" respectively through "1.5μm, 1.7μm, 2.0μm, 2.3μm, and 2.5μm" quantum dot films;

[0077] The process of preparing "strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers" respectively through "1.5μm, 1.7μm, 2.0μm, 2.3μm, and 2.5μm" quantum dot films includes:

[0078] Preparation of 1.5μm strong P-type film, preparation of 1.7μm secondary P-type film, preparation of 2.0μm weak P-type film, preparation of 2.3μm intrinsic type film, and preparation of 2.5μm N-type film.

[0079] Further, the process of preparing the PVP layer includes:

[0080] In order to combine quantum dot films of different doping states, the present invention introduces polyvinyl pyrrolidone (PVP) polymer, dissolves the polyvinyl pyrrolidone polymer in ethanol with a concentration of 0.1M, and spin-coats it on a sapphire Al2O3 substrate at 3000r / min;

[0081] After curing on a hot plate at 50°C for 5 min, the entire sheet was peeled off from the sapphire substrate to obtain the target polymer;

[0082] The quantum dot film is coated on the surface of the target polymer to assemble the quantum dot film.

[0083] Furthermore, the preparation process of the 1.5 μm strong P-type film includes:

[0084] On the sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as the substrate of the PV type device. After the PVP polymer was spin-coated on the substrate, a 100nm thick, 1.5μm quantum dot film was spin-coated on the target polymer surface at a speed of 2000r / min. Then, the whole was placed in a ventilation device and treated with a 15% AsH3 / N2 mixed gas for 2min to obtain a strong P-type doped film.

[0085] The preparation process of 1.7μm P-type film includes:

[0086] On the sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as the substrate of the PV type device. After the PVP polymer was spin-coated on the substrate, a 100nm thick, 1.7μm quantum dot film was spin-coated on the target polymer surface at a speed of 2000r / min. Then, the whole was placed in a ventilation device and treated with a 10% AsH3 / N2 mixed gas for 2min to obtain a sub-P type doped film.

[0087] The preparation process of 2.0μm weak P-type film includes:

[0088] On the sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as the substrate of the PV type device. After the PVP polymer was spin-coated on the substrate, a 100nm thick, 2.0μm quantum dot film was spin-coated on the target polymer surface at a speed of 2000r / min. Then, the whole was placed in a ventilation device and treated with a 2% AsH3 / N2 mixed gas for 2min to obtain a weak P-type doped film.

[0089] The preparation process of 2.3μm intrinsic film includes:

[0090] On a sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as the substrate of the PV device. After spin coating the PVP polymer on the substrate, a 200nm thick, 2.3μm quantum dot film was spin coated on the target polymer surface at a speed of 1000r / min, and then the whole was placed in a ventilation device and treated with a 1% Cl2 / N2 mixed gas for 2min to obtain an intrinsic doped film.

[0091] The preparation process of 2.5μm N-type film includes:

[0092] The N-type layer is the bottom layer of the device and does not need to be peeled off for transfer, so there is no need to coat the PVP layer. On the sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) is magnetron sputtered as the substrate of the PV type device. A 100nm thick, 2.5μm quantum dot film is directly spin-coated on the substrate at a speed of 2000r / min, and then the whole is placed in a ventilation device and treated with a 2% Cl2 / N2 mixed gas for 2 minutes to obtain an N-type doped film.

[0093] The present invention realizes dual gradient regulation of band gap and doping through the above operation, and the structural schematic diagram of preparing thin films of different doping types is shown as follows: Figure 1 The FET curve of the obtained film is shown in Figure 2 shown.

[0094] Furthermore, if Figure 3 As shown, the process of preparing an infrared spectroscopy device with a bandgap doped double gradient PN junction includes:

[0095] Based on the N-type layer, the 2.3μm intrinsic layer film was peeled off from the sapphire substrate, and the N-type layer and the intrinsic layer were treated with ethylenedithiol / isopropanol / hydrochloric acid (EDT / IPA / HCl) with a volume ratio of 1:1:50 for 10s respectively to remove the excess ligands on the surface and the stable Fermi level; the film was not blown dry, and the ligands and van der Waals forces still existed on the surface, and the intrinsic layer film surface with PVP polymer was closely attached to the N-type film surface to obtain the first assembly; the surface of the first assembly was then blown dry with an air gun and soaked in ethanol for 5s to remove the PVP polymer, thereby obtaining the superposition of two layers of films with different doping states;

[0096] Based on the superposition of two layers of thin films with different doping states, a 2.0 μm weak P-type thin film was peeled off from the sapphire substrate, and the 2.0 μm weak P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the weak P-type film surface with PVP polymer was closely attached to the 2.3 μm intrinsic layer film on the upper surface of the first assembly to obtain a second assembly; the surface of the second assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a superposition of three layers of thin films with different doping states;

[0097] Based on the stacking of three layers of thin films with different doping states, the 1.7μm sub-P-type thin film was peeled off from the sapphire substrate, and the sub-P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10s, and the sub-P-type thin film surface with PVP polymer was closely attached to the 2.0μm weak P-type thin film on the upper surface of the second assembly to obtain the third assembly; the surface of the third assembly was then dried with an air gun and soaked in ethanol for 5s to remove the PVP polymer, thereby obtaining the stacking of four layers of thin films with different doping states;

[0098] Based on the superposition of four layers of thin films with different doping states, a 1.5μm strong P-type thin film was peeled off from the sapphire substrate, and the strong P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10s without blowing the film dry. At this time, ligands and van der Waals forces still existed on the surface. The surface of the sub-P-type thin film with PVP polymer was closely attached to the 1.7μm sub-P-type thin film on the upper surface of the third assembly to obtain the fourth assembly; the surface of the fourth assembly was then dried with an air gun and soaked in ethanol for 5s to remove the PVP polymer, thereby obtaining the superposition of five layers of thin films with different doping states;

[0099] Then, 50 nm of gold (Au) was evaporated on the top as a contact point to prepare an infrared spectroscopy device with a bandgap doped double-gradient PN junction.

[0100] like Figure 4-5 As shown, this embodiment utilizes the quantum confinement effect of colloidal quantum dots, regulates the band gap by size, and designs a P-graded-N junction, in which the P-graded doping material is composed of short-wave quantum dots with different band gaps. From the P-graded-N junction, the band gap gradually decreases. When the reverse bias is very small, only the larger band gap quantum dot layer is depleted (strong P layer-sub-P layer or strong P layer-sub-P layer-weak P layer), and only the carriers generated by the shorter wavelength incident light and absorbed by the large band gap quantum dot layer can be effectively collected and promote the photocurrent. The holes generated in the narrow band gap quantum dot layer (intrinsic layer or N layer) generated by the longer wavelength incident light are blocked by the valence band barrier of the large band gap quantum dot layer, and therefore cannot effectively contribute to the photocurrent. As the reverse bias increases, the depletion region (strong P type-sub-strong P type-weak P type-intrinsic type-N type layer) extends to the narrower quantum dot layer, and these carriers generated by the longer wavelength incident light can be collected and contribute to the photocurrent. The smaller the band gap, the longer the extended wavelength. Therefore, the voltage-tunable spectral responsivity can be obtained as Figure 6 As shown, the spectral resolution depends on the bias voltage, and the actual spectral resolution is 6nm (18cm -1 ).

[0101] The present invention uses atmosphere treatment to achieve different doping concentrations and types of quantum dot films, and designs a detector structure of "strong P-type-sub-strong P-type-weak P-type-intrinsic type-N-type layer". The gradient doped PN junction detector is biased and regulated. As the bias increases, the band gap increases from a large band gap to a small band gap. Different band gaps correspond to different wavelengths, forming a doping band gap dual gradient regulation, and realizing the response of the infrared detector to spectra of different bands.

[0102] The present invention does not require complicated spectroscopic optical paths or microstructures such as filters designed for specific spectral bands. The spectrum can be resolved by simply adjusting the bias voltage of the detector, while achieving miniaturization and high photon utilization efficiency.

[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction, characterized in that: include: By using surface ligands to control the doping concentration and type of quantum dot films, the detector structures of "strong P-type-sub-strong P-type-weak P-type-intrinsic type-N-type layer" and "large band gap-medium-large band gap-medium band gap-medium-small band gap-small band gap" are designed; By using bias voltage regulation, different responses of quantum dot gradient doped PN junction infrared detectors to different spectra are achieved, and an infrared spectroscopy device with a bandgap doped double gradient PN junction is prepared. The synthesis process of the quantum dots comprises: In a glove box under a nitrogen environment, 27 mg and 0.1 mmol of mercuric chloride (HgCl2) were taken, and 4 ml of oleylamine (OAM) was added to obtain a mixture; the mixture was placed on a hot plate, stirred with a magnetic stirrer, and the temperature of the hot plate was adjusted to 105° C., and heated at 105° C. for 1 h until a transparent light yellow solution was formed; Take 500 μL TOP, 500 μL DDT, and 4 mL TCE into a glass bottle and store it in a refrigerator to prepare a quenching solution; After the transparent light yellow solution becomes clear, the reaction temperature is lowered as required by the hot injection method, and the thermal equilibrium is maintained for half an hour. After the thermal equilibrium is completed, 100 μL of TOPTe solution is injected, and the reaction is continued for a preset reaction time as required. After the reaction is completed, the quenching solution is added to cool the reaction, and the solution is taken out from the glove box and cooled in a water bath to obtain short-wave quantum dots; The synthesis of the quantum dots comprises: Synthesis of 1.5μm short-wave quantum dots, synthesis of 1.7μm short-wave quantum dots, synthesis of 2.0μm short-wave quantum dots, synthesis of 2.3μm short-wave quantum dots, and synthesis of 2.5μm short-wave quantum dots; The reaction temperature for synthesizing the 1.5 μm short-wavelength quantum dots was 55° C. and the reaction time was 4 min. The reaction temperature for synthesizing the 1.7 μm short-wavelength quantum dots is 60° C. and the reaction time is 4 min. The reaction temperature for synthesizing the 2.0 μm short-wavelength quantum dots is 65° C. and the reaction time is 5 min. The reaction temperature for synthesizing the 2.3 μm short-wavelength quantum dots was 75° C. and the reaction time was 4 min. The reaction temperature for synthesizing the 2.5 μm short-wavelength quantum dots is 80° C. and the reaction time is 4 min. The preparation process of the "strong P type-secondary strong P type-weak P type-intrinsic type-N type layer" includes: Prepare a PVP layer, and based on the PVP layer, prepare "strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers" respectively through "1.5 μm, 1.7 μm, 2.0 μm, 2.3 μm, and 2.5 μm" quantum dot films; The process of preparing "strong P-type, sub-strong P-type, weak P-type, intrinsic type, and N-type layers" respectively through "1.5μm, 1.7μm, 2.0μm, 2.3μm, and 2.5μm" quantum dot films includes: Preparation of 1.5μm strong P-type film, 1.7μm sub-P-type film, 2.0μm weak P-type film, 2.3μm intrinsic film, and 2.5μm N-type film; The process of preparing the PVP layer comprises: Polyvinyl pyrrolidone polymer was dissolved in ethanol with a concentration of 0.1 M and spin-coated on a sapphire Al2O3 substrate at 3000 r / min; After curing on a hot plate at 50°C for 5 min, the entire sheet was peeled off from the sapphire substrate to obtain the target polymer; Coating a quantum dot film on the surface of the target polymer to assemble the quantum dot film; The preparation process of the 1.5 μm strong P-type film includes: On a sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100nm thick, 1.5μm quantum dot film was spin coated on the target polymer surface at a speed of 2000r / min, and then the whole was placed in a ventilation device and treated with a 15% AsH3 / N2 mixed gas for 2min to obtain a strong P-type doped film; The preparation process of the 1.7 μm P-type thin film includes: On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100 nm thick, 1.7 μm quantum dot film was spin coated on the target polymer surface at a speed of 2000 r / min. The whole was then placed in a ventilation device and treated with a 10% AsH3 / N2 mixed gas for 2 minutes to obtain a sub-P type doped film. The preparation process of the 2.0 μm weak P-type thin film includes: On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 100 nm thick, 2.0 μm quantum dot film was spin coated on the target polymer surface at a speed of 2000 r / min. The whole was then placed in a ventilation device and treated with a 2% AsH3 / N2 mixed gas for 2 minutes to obtain a weak P-type doped film. The preparation process of the 2.3 μm intrinsic film includes: On a sapphire Al2O3 substrate, 50 nm of indium tin oxide (ITO) was magnetron sputtered as a substrate for a PV type device. After spin coating a PVP polymer on the substrate, a 200 nm thick, 2.3 μm quantum dot film was spin coated on the target polymer surface at a speed of 1000 r / min, and then the whole was placed in a ventilation device and treated with a 1% Cl2 / N2 mixed gas for 2 minutes to obtain an intrinsic type doped film; The preparation process of the 2.5 μm N-type thin film includes: On the sapphire Al2O3 substrate, 50nm of indium tin oxide (ITO) was magnetron sputtered as the substrate of the PV type device, and a 100nm thick, 2.5μm quantum dot film was directly spin-coated on the substrate at a speed of 2000r / min, and then the whole was placed in a ventilation device and treated with a 2% Cl2 / N2 mixed gas for 2min to obtain an N-type doped film; The process of preparing an infrared spectroscopy device with a bandgap doped double gradient PN junction includes: Based on the N-type layer, a 2.3 μm intrinsic layer film was peeled off from the sapphire substrate, and the N-type layer and the intrinsic layer were treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds respectively to remove excess surface ligands and stable Fermi levels; without blowing the film dry, the intrinsic layer film surface with the PVP polymer was placed close to the N-type film surface to obtain a first assembly; the surface of the first assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a superposition of two layers of films with different doping states; Based on the superposition of two layers of thin films with different doping states, a 2.0 μm weak P-type thin film was peeled off from the sapphire substrate, and the 2.0 μm weak P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the weak P-type film surface with PVP polymer was closely attached to the 2.3 μm intrinsic layer film on the upper surface of the first assembly to obtain a second assembly; the surface of the second assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a superposition of three layers of thin films with different doping states; Based on the stacking of three layers of thin films with different doping states, a 1.7 μm sub-P-type thin film was peeled off from a sapphire substrate, and the sub-P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the sub-P-type thin film surface with PVP polymer was closely attached to the 2.0 μm weak P-type thin film on the upper surface of the second assembly to obtain a third assembly; the surface of the third assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a stacking of four layers of thin films with different doping states; Based on the stacking of four layers of thin films with different doping states, a 1.5 μm strong P-type thin film was peeled off from the sapphire substrate, and the strong P-type thin film was first treated with ethanedithiol / isopropanol / hydrochloric acid in a volume ratio of 1:1:50 for 10 seconds, and the surface of the sub-P-type thin film with PVP polymer was closely attached to the 1.7 μm sub-P-type thin film on the upper surface of the third assembly to obtain a fourth assembly; the surface of the fourth assembly was then dried with an air gun and soaked in ethanol for 5 seconds to remove the PVP polymer, thereby obtaining a stacking of five layers of thin films with different doping states; Then, 50 nm of gold (Au) was evaporated on the top as a contact point to prepare an infrared spectroscopy device with a bandgap doped double-gradient PN junction.

2. The method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction according to claim 1, characterized in that: Using surface ligands to control the doping concentration and type of quantum dot films also includes material preparation; The material preparation includes preparing 90% tri-n-octyl phosphide (TOP) with a technical grade of 90%, 99.999% granular tellurium (Te), ACS reagent grade>=99.5% mercuric chloride (HgCl2), 70% oleylamine (OAM), 98% dodecanedetate (DDT), HPLC99.9% tetrachloroethylene (TCE), and preparing TOPTe solution.

3. The method for preparing an infrared spectroscopy device with bias-controlled quantum dot gradient-doped PN junction according to claim 2, characterized in that: The preparation process of the TOPTe solution includes: stirring tellurium (Te) particles and tri-n-octylphosphine (TOP) in a nitrogen glove box at room temperature to prepare a Te solution dissolved in tri-n-octylphosphine (TOP) to form a bright yellow solution with a concentration of 1M, which is the TOPTe solution.

Citation Information

Patent Citations

  • Double-gradient regulation and control quantum dot photovoltaic detector and preparation method thereof

    CN115939237A

  • Double-color tellurium-cadmium-mercury infrared photoelectric detector and preparation method thereof

    CN116387393A